2005
DOI: 10.1016/j.cell.2005.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic BID Is an ATM Effector in the DNA-Damage Response

Abstract: The "BH3-only" proapoptotic BCL-2 family members are sentinels of intracellular damage. Here, we demonstrated that the BH3-only BID protein partially localizes to the nucleus in healthy cells, is important for apoptosis induced by DNA damage, and is phosphorylated following induction of double-strand breaks in DNA. We also found that BID phosphorylation is mediated by the ATM kinase and occurs in mouse BID on two ATM consensus sites. Interestingly, BID-/- cells failed to accumulate in the S phase of the cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
221
10
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(246 citation statements)
references
References 17 publications
14
221
10
1
Order By: Relevance
“…62 These abnormal chromosomal structures represent 'chromatid-type' errors, resulting from improperly repaired DNA damage accrued during S phase of the cell 62 Bid À/À myeloid progenitor cells and MEFs fail to properly execute the ionizing radiation-induced intra-S-phase checkpoint. 62,63 This Sphase role is mediated through BID phosphorylation at position 78 by the DNA damage kinase ATM, demonstrating a direct link between BID and the DNA damage response. These studies demonstrate that BID plays a novel role in preserving genomic integrity that places BID at an early point in the path to determine the fate of a cell (Figure 2).…”
Section: Proapoptotic Bidmentioning
confidence: 92%
See 2 more Smart Citations
“…62 These abnormal chromosomal structures represent 'chromatid-type' errors, resulting from improperly repaired DNA damage accrued during S phase of the cell 62 Bid À/À myeloid progenitor cells and MEFs fail to properly execute the ionizing radiation-induced intra-S-phase checkpoint. 62,63 This Sphase role is mediated through BID phosphorylation at position 78 by the DNA damage kinase ATM, demonstrating a direct link between BID and the DNA damage response. These studies demonstrate that BID plays a novel role in preserving genomic integrity that places BID at an early point in the path to determine the fate of a cell (Figure 2).…”
Section: Proapoptotic Bidmentioning
confidence: 92%
“…Casein kinases have been implicated in BID phosphorylation, and ATM has been shown to phosphorylate BID following DNA damage. [61][62][63] Phosphorylated BID is resistant to caspase cleavage in in vitro assays, and MEFs harboring phosphorylation-defective S78A BID are more sensitive to etoposide-induced cell death. The above data are consistent with a role for phosphorylation to inhibit activation of BID's proapoptotic function.…”
Section: Proapoptotic Bidmentioning
confidence: 99%
See 1 more Smart Citation
“…57 In addition to these internal familybased interactions, BCL-2 proteins associate with a host of other cellular proteins 31,47,[63][64][65][66][67][68][69][70][71] and have emerging roles in diverse physiologic pathways including glucose metabolism 20 and the DNA-damage response. 24,40 …”
Section: Introductionmentioning
confidence: 99%
“…1 Previously we have reported that DNA damage induces the phosphorylation of BID on serines 61 and 78 by the ataxia-telangiectasia mutated (ATM) kinase, and that this phosphorylation is important for cell cycle arrest and inhibition of apoptosis. 2 In addition, another group reported similar results in response to replicative stress. 3 Nevertheless, these findings were challenged by a third group, which demonstrated that in response to DNA damage BID −/− cells underwent cell cycle arrest and apoptosis in a manner indistinguishable from wild-type cells, arguing that BID is dispensable for the DDR.…”
mentioning
confidence: 81%